2004
DOI: 10.1002/elan.200303036
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an Electronic Nose with the Sensory Evaluation of Food Products by “Triangle Test”

Abstract: In this paper a novel approach for performing discriminative test in food quality control is reported. The method is based on the use of an electronic nose equipped with 10 Metal Oxide Semiconductor Field Effect Transistor (MOSFET) sensors, 12 Metal Oxide Semiconductor (MOS) sensors and one humidity sensor. The pattern of the sensor responses generated by the electronic nose has been used for performing "objective" triangle tests in several food products. The results were compared with the data obtained by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…Parmigiano Reggiano and Pecorino Romano were also discriminated from each other. Using a different kind of electronic nose, Benedetti et al (2004) also found similar results for these cheese varieties. Processing technology for Grana and Grana Padano cheeses have similarities although the former is produced in Finland and the latter in Italy.…”
Section: Discrimination Of Cheeses By Varietysupporting
confidence: 80%
“…Parmigiano Reggiano and Pecorino Romano were also discriminated from each other. Using a different kind of electronic nose, Benedetti et al (2004) also found similar results for these cheese varieties. Processing technology for Grana and Grana Padano cheeses have similarities although the former is produced in Finland and the latter in Italy.…”
Section: Discrimination Of Cheeses By Varietysupporting
confidence: 80%
“…However, the variation was random and not significant; high standard deviation was found across various sample volumes (50-500 L) but not across vials in the carousel. This was also confirmed in the literature [32,33]. Almost all MOSFET sensors of e-nose 1 were found to be replicate dependent and almost all MOS sensors varied over time.…”
Section: Mosfet/mos E-nose Characterisationsupporting
confidence: 74%
“…All of these techniques are time-consuming and expensive and electronic noses and tongues are not selective. 2,3,5,11,13,14,23 The brewing of beer is a typical example of a food production process. Despite economic interests such as cost reduction and short duration of the production process, the product quality should be assured for the consumer with regard to taste.…”
Section: Introductionmentioning
confidence: 99%